1971
DOI: 10.1002/j.1551-8833.1971.tb04023.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality vs. Residual Chlorine

Abstract: Chlorine residual, an indication of adequate chlorination of a water supply, has a definite relationship with the bacteriological quality of the supply. This paper discusses how much, what kind of, and the proper surveillance of, chlorine residual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Subsequently, in Section 141.21(h) of the 1975 National Interim Primary Drinking Water Regulations, the US Environmental Protection Agency (USEPA) (1975) allowed a free chlorine residual to be substituted for 75% of the required coliform samples with approval of the state and based on a sanitary survey, requiring the free chlorine concentration to be “no less than 0.2 mg/L free chlorine throughout the public water distribution system.” The background for the substitution of residual free chlorine measurement for total coliform measurement was provided by USEPA (1976) and relied on the previous studies of McCabe et al (1970) and Buelow and Walton (1971) to justify this decision.…”
Section: Distribution System Residualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, in Section 141.21(h) of the 1975 National Interim Primary Drinking Water Regulations, the US Environmental Protection Agency (USEPA) (1975) allowed a free chlorine residual to be substituted for 75% of the required coliform samples with approval of the state and based on a sanitary survey, requiring the free chlorine concentration to be “no less than 0.2 mg/L free chlorine throughout the public water distribution system.” The background for the substitution of residual free chlorine measurement for total coliform measurement was provided by USEPA (1976) and relied on the previous studies of McCabe et al (1970) and Buelow and Walton (1971) to justify this decision.…”
Section: Distribution System Residualsmentioning
confidence: 99%
“…McCabe et al (1970) showed that unless a chlorine residual was maintained in the distribution system, a significant number of samples would not meet the bacteriological standard. Subsequently, Buelow and Walton (1971) investigated the validity that a chlorine residual might serve as a substitute for total coliform measurements. Buelow and Walton (1971) provided data supporting “that many of the bacteriological samples currently collected could be eliminated provided chlorine residual can be shown to be present throughout a distribution system,” and in the Cincinnati, Ohio, distribution system, they found that maintaining a free chlorine residual of 0.2 mg/L reduced coliform positives to about 1%.…”
Section: Distribution System Residualsmentioning
confidence: 99%